From the urban metabolism to the urban immune system. (13th June 2019) - Bristow, David N.; Mohareb, Eugene A.
Abstract: Urban areas face mounting risks from many sources. Cities pursue myriad tactics to resist, recover from and adapt to shocks and stresses, but little is known about how these approaches relate across the scales of a city nor how cities compare in their abilities. Part of the challenge in addressing these gaps is that the risk to cities is typically studied with an emphasis on one or a few hazards or through the lens of a singular sector. This paper proposes a framework, dubbed the Urban Immune System (UIS) to coalesce and expand industrial ecology research on urban risk management. In the same way that Urban Metabolism (UM) is a unifying framework for urban environmental sustainability, UIS can be a unifying framework for urban resilience, especially related to climate change. Herein, UIS is defined, its many capabilities are dissected and linked to disparate studies; and opportunities for application of the concept are provided. The paper concludes by examining the relationship between UIS and climate change and by identifying those attributes of the UIS that are expected to be of increasing importance under climate change.